A study on some relations on multi-fuzzy (left-right)ideals of rings - Saleem , Kholoud. W.; Abu-harbid, Suzan. A. A.; Tentush , Abrahim.A. A. (Journal of Pure & Applied Sciences, 2021)
multi fuzzy set theory is an extension of fuzzy set theory, which deals with the multi dimensional fuzziness. In this paper, we introduce the concepts of multi-fuzzy rings, multi fuzzy ideal, image of multi- fuzzy ideal of a ring under homomorphism, Cartesian product of multi-fuzzy set, and some related properties and theorems are investigated. The purpose of this study is to implement the fuzzy set theory and rings theory in multi-fuzzy rings.